Teachers' assistance to pupils with insufficient knowledge of the instruction language - Kropacova, Jitka (e-Pedagogium, 2005)
The paper deals with the problems of pupils in bilingual environments who have insufficient knowledge of the instruction language. The quantitative Q-method procedures were used to gather findings that can enable teachers to assist pupils in such situations.
Keywords: Bilingualism; language skills; communication; educational methods; teacher-pupil relation